The Role of Lubuk Larangan as a Biology Learning Media for Conservation Material to Improve Environmental Literacy: Systematic Literature Review - Ngade Wantara; Necta Ayu Cahyanti; Suhartini Suhartini; Muhammad Rasyid; Habibatul Unayah (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2026)
This study aims to examine the potential of Lubuk Larangan as a biology learning resource to support the development of students’ environmental literacy. The study employed a Systematic Literature Review (SLR) method by analyzing scholarly articles obtained from major academic databases such as Google Scholar, Scopus-indexed journals, and national indexed journals. An initial search identified 100 relevant articles, which were then screened and evaluated using predefined inclusion and exclusion criteria, resulting in 11 articles selected for in-depth analysis. The findings indicate that Lubuk Larangan provides a meaningful contextual learning environment where students can directly explore ecological concepts such as ecosystems, biodiversity, and sustainable resource management. Integrating this local wisdom into biology learning supports the development of environmental awareness, critical thinking, and collaborative problem-solving skills. Moreover, the use of Lubuk Larangan aligns with the principles of 21st-century education that emphasize contextual, experiential, and community-based learning. This study therefore recommends integrating Lubuk Larangan into the biology curriculum as a strategy to strengthen environmental literacy and promote conservation values. Effective implementation requires collaboration among educational institutions, local communities, and government stakeholders to ensure sustainable conservation practices and meaningful environmental education in Indonesia.